Estudio del contenido que el Gobierno Autónomo Descentralizado del cantón Pindal, difundió a través de la red social Facebook para promocionar el turismo en el año 2021. - Moncada Calderón, Cindy Brigitte (2023)
Tourism has become the key engine to achieve socioeconomic progress in many countries, which is why today it has been modernized and have chosen to make tourism with different digital platforms. The present research work is focused on the study of the content that was disseminated through the social network Facebook of the Decentralized Autonomous Government of the canton Pindal, for tourism promotion in the year 2021, in order to analyze the digital content that is promoted on the social network Facebook and measure the effectiveness of publications. The study includes a literature review, where theories and concepts that support this work have been compiled. Likewise, the methodology used is of mixed approach since both quantitative and qualitative methods were integrated, taking into consideration the following techniques: surveys, observation sheets, interviews and content analysis. The results show that the people in charge of the Communication Department of the GAD of Pindal canton have little knowledge about the use of the social network Facebook in relation to tourism promotion, which causes the @nuevomunicipiodepindal account to lack impacting content and thus fails to generate interest in its audience. Finally, the conclusions, recommendations and alternative proposal given to the Autonomous Decentralized Municipal Government of Pindal for the promotion of tourism in Pindal and its parishes are presented. Keywords: GAD-Pindal; Tourism promotion; Communication and tourism; Tourism in social networks; Facebook.